2015
DOI: 10.1589/jpts.27.1133
|View full text |Cite
|
Sign up to set email alerts
|

Does whole-body vibration training in the horizontal direction have effects on motor function and balance of chronic stroke survivors? A preliminary study

Abstract: [Purpose] The objective of this study was to investigate the effects of whole-body vibration (WBV) in the horizontal direction on the motor function and balance of chronic stroke survivors. [Subjects and Methods] This study was a randomized controlled trial. Twenty-one individuals with chronic stroke from an inpatient rehabilitation center participated in the study. The participants were allocated to either the WBV training group or the control group. The WBV training group (n = 12) received whole-body vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 29 publications
1
29
0
2
Order By: Relevance
“…Whole body vibration (WBV) is a novel rehabilitative exercise that uses low amplitude, low frequency vibration administered through a platform or Power Plate. WBV shows potential as an effective therapeutic approach and has been studied in a variety of clinical settings that include rehabilitation of patients with chronic stroke [8], spinal cord injury [9], lumbar disk disease and lower back pain syndromes [10], Parkinson's disease [11], elderly with sarcopenia [12,13], chronic obstructive pulmonary disease (COPD) [14 ], multiple sclerosis [15], obesity, osteoporosis, osteoarthritis and fibromyalgia [16] and children with cerebral palsy [17]. A growing body of evidence in laboratory animals and patients with chronic stroke have shown that WBV reduces or reverses pathological remodeling of bone and such a treatment could also help reduce frailty related physiological deterioration [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Whole body vibration (WBV) is a novel rehabilitative exercise that uses low amplitude, low frequency vibration administered through a platform or Power Plate. WBV shows potential as an effective therapeutic approach and has been studied in a variety of clinical settings that include rehabilitation of patients with chronic stroke [8], spinal cord injury [9], lumbar disk disease and lower back pain syndromes [10], Parkinson's disease [11], elderly with sarcopenia [12,13], chronic obstructive pulmonary disease (COPD) [14 ], multiple sclerosis [15], obesity, osteoporosis, osteoarthritis and fibromyalgia [16] and children with cerebral palsy [17]. A growing body of evidence in laboratory animals and patients with chronic stroke have shown that WBV reduces or reverses pathological remodeling of bone and such a treatment could also help reduce frailty related physiological deterioration [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Literature search, study characteristics and quality assessment Among the 8 studies included here, 3 studies report 6MWT distance [11,14,22], 4 studies report TUG test [11,13,14,17], 2 studies report Fugl-Meyer assessment [17,18], three studies report Berg Balance Scale [14,17,22], and 2 studies report ABC scale [11,22]. The detail for risk of bias tool are shown in ▶ fig.…”
Section: Resultsmentioning
confidence: 99%
“…volve whole-body vibration in the horizontal direction, and reports the significantly positive influence on the rehabilitation of stroke patients [17]. More studies should be conducted to investigate the clinical significance of whole-body vibration training.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations